'She was really good at letting us make decisions:' influence of purposefully negotiating the physical education curriculum on one teacher and a boys' middle school minority class. Issue 2 (4th May 2019) - Guadalupe, Tasha; Curtner-Smith, Matthew D.
ABSTRACT: A limited amount of research indicates that when teachers purposefully invite students to negotiate the physical education curriculum, students have a more equitable experience. The primary purpose of this study was to investigate the impact of purposefully negotiating the curriculum on one boys' physical education class. A second purpose was to assess the effectiveness of the program that was used to train the teacher of the class to engage in purposeful negotiation. Participants were the 32 seventh grade boys in the class and Sandra, their teacher. The theoretical framework was drawn from elements within the critical tradition and the perspective of hegemonic masculinity. Data were collected with seven qualitative techniques and analysed using analytic induction and constant comparison. The negotiated unit that Sandra taught and the program that trained her were a qualified success. Non-masculine less physically able boys engaged in and enjoyed the unit to a greater degree than was usual. Some usually dominant physically able boys showed more empathy for their less skilled peers. More negatively, the curriculum model employed, activity chosen, content, and evaluation methods selected, all of which reflected a traditional performance pedagogy, were constraining.